Glutamate hypothesis in schizophrenia - Uno, Yota; Coyle, Joseph T. (Psychiatry and clinical neurosciences, 2019)
Schizophrenia is a chronic and severe psychiatric disorder that has profound impact on an individual’s life and on society. Thus, developing more effective therapeutic interventions is essential. Over the past quarter‐century, an abundance of evidence from pharmacologic challenges, post‐mortem studies, brain imaging, and genetic studies supports the role of glutamatergic dysregulation in the pathophysiology of schizophrenia, and the results of recent randomized clinical trials based on this evidence have yielded promising results. In this article, we review the evidence that alterations in glutamatergic neurotransmission, especially focusing on the N‐methyl‐d‐aspartate receptor (NMDAR) function, may be a critical causative feature of schizophrenia, how this contributes to pathologic circuit function in the brain, and how these insights are revealing whole new avenues for treatment development that could reduce treatment‐resistant symptoms, which account for persistent disability.